Tourism branding of cities and territories - Basyuk, Daria; Melnyk, Y. (My University, 2014)
Branding cities and territories is a vibrant area now where regions, towns and cities are trying to present themselves to different audiences, usually for tourism.
Keywords: branding; tourism; брендінг; туризм; брендинг; кафедра іноземних мов професійного спрямування; кафедра туристичного та готельного бізнесу